Mechanism of action of total saponin Achyranthes in treating knee osteoarthritis explored using network pharmacology and animal experimentation - Shiwei Zhuang; Qiang Chen; Xiao Guo; Wenhai Zhao; Ye Qiu (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Knee osteoarthritis (KOA) is a persistent degenerative disease affecting the joints, significantly reducing the quality of life for individuals afflicted. This study explores the therapeutic effects of total  saponin Achranthes (TSA) on KOA rats and its underlying mechanism. Materials and Methods: Forty-eight rats were randomly assigned to six experimental groups: a blank control group, a model group, a sham-operated group, and a TSA treatment group (low, medium, and high dose), with eight rats in each group. The rats were treated continuously for four weeks. The degree of joint swelling was quantified, and the Lequesne MG score was evaluated. Network pharmacology approaches were employed to pinpoint potential TSA targets and related pathways for managing KOA. Additionally, histopathological examinations were conducted on the knee cartilage of the rats. Serum levels of TNF-α and IL-1β were assessed through the ELISA assay. Results: The network pharmacology results indicate that TSA may effectively treat KOA through the MAPK and PI3K/Akt signaling pathways. Moreover, TSA significantly decreased the serum concentrations of pro-inflammatory cytokines such as TNF-α and IL-1β, and  TSA down-regulated the P38 MAPK, PI3K/Akt, and NF-κB pathways, whereas the KOA model showed up-regulation. The treatment also significantly reduced MMP-9, MMP-13, and ADAMTS-5 protein levels.Conclusion: TSA can potentially ameliorate inflammation, safeguard knee cartilage tissue, and alleviate symptoms of KOA by inhibiting the MAPK/Akt/NF-κB signaling pathway.